Pengaruh Opini Audit, Audit Fee, Reputasi KAP dan Ukuran Perusahaan Klien Terhadap Auditor Switching - Widnyani, Ni Luh Eka Desy; RM, Ketut Muliartha (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p12, 2018)
The company's need for audit services causes competition between public accounting firms to get clients. In order to maintain the reliability of the financial statements and the independence of auditors it is necessary to apply auditors switching. The purpose of this study is to determine the effect of audit opinion, audit fee, reputation KAP and the size firms to the auditor switching. The method of determining the sample was done by using purposive samplings technique, get samples of 20 companies. Data collection method used in this research is documentation method. Data analysis technique used to test the hypothesis is logistic regression analysis with the help of the SPSS program. The result of analysis shows that audit opinion does not affect auditor switching, audit fee have positive effect to auditor switching, KAP reputation has no effect to auditor switching and size firm negative affect auditor switching. Keywords : audit opinion, audit fee, KAP reputation and size firm